2020
DOI: 10.1111/mcn.12961
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality among pregnant women in the Navajo Birth Cohort Study

Abstract: Proper nutrition during pregnancy is vital to maternal health and fetal development and may be challenging for Navajo Nation residents because access to affordable and healthy foods is limited. It has been several decades since reported diet quality during pregnancy was examined on Navajo Nation. We present the first study to estimate iodine intake and use the Healthy Eating Index (HEI‐2015) to assess maternal diet quality among pregnant women in the Navajo Birth Cohort Study (NBCS). Based on dietary intake da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…Similarly to us, a limitation about the application of the HEI-2015, intending to assess sodium intake, was already noticed, since this instrument was not designed to this aim [15]. In pregnant from the NBCS cohort and with lower insu cient iodine status it was also not demonstrated different scores in the component sodium of HEI-2015 in comparison to pregnant women from HNANES and with adequate iodine status [15].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly to us, a limitation about the application of the HEI-2015, intending to assess sodium intake, was already noticed, since this instrument was not designed to this aim [15]. In pregnant from the NBCS cohort and with lower insu cient iodine status it was also not demonstrated different scores in the component sodium of HEI-2015 in comparison to pregnant women from HNANES and with adequate iodine status [15].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, excessive UIC was related to worse intake of "whole fruits" and "total vegetables". As previously noted, data in literature regarding the relationship diet quality and iodine status are scarce [15]. A study evaluating pregnant women in the Navajo Birth Cohort Study (NBCS) demonstrated that they had lower UIC than pregnant from the National Health and Nutrition Examination Survey (NHANES), with higher risk for iodine insu ciency [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our partial results are similar to a systematic review indicating that the great recession of 2008 caused a decrease in consumptions of foods such as fruit and vegetable ( 35 ). Two studies ( 36 , 37 ) conducted in the Navajo nation found that access to and availability of foods are particularly important and determine food consumption. It is possible that during the COVID-19 pandemic, there was reduced consumption of foods with short shelf lives related to the number of shopping opportunities and locations.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we also considered the effects of the micronutrients iodine, zinc, and selenium. These micronutrients are important for normal growth but deficient in our population [ 29 ]. Iodine deficiency has been recognized as detrimental and damaging for organogenesis and brain development in the fetus [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%